The Risks and Opportunities of Forming a Specific Business Environment in Ukraine in the Conditions of War - Maryana Melnyk; Iryna Leshchukh; Uliana Ivaniuk (Studia Regionalne i Lokalne)
The research analyses a range of analytical materials of Ukrainian and international experts in business, economy, finance, etc., and the data of sociological surveys of the representatives of Ukrainian businesses regarding the entrepreneurship development trends in Ukraine in conditions of martial law. The analysis of these resources has revealed a substantial negative impact of the war on the export of goods and services from Ukraine, the falling sales volumes, the reducing staff of enterprises, problems with labour remuneration, and the preservation of panic in the business environment. However, there is a substantial risk that the hostilities do not end in the short run. Therefore, the authors analyse the opportunities for the creation of a specific business environment in Ukraine under martial law with the view to develop a policy directed at securing economic resilience as well as the maintenance of the country’s economic capacity. The risks and threats of doing business in Ukraine in the context of adopted amendments to legislation in conditions of war are examined. The priority steps for the elimination of possible threats of falling business activity are outlined.